Investigating the factors affecting the investment decision in residential development. - Narang, Somil (2007)
The purpose of this project is to provide a rare insight into the motivation behind residential property investors when looking to purchase an apartment. The factors driving demand preferences for housing are constantly changing, difficult to measure, and often deemed to be a complex bundle of attributes. The project attempts to answer the following questions: